2022
DOI: 10.3389/fnbeh.2022.837654
|View full text |Cite
|
Sign up to set email alerts
|

Large-N Rat Data Enables Phenotyping of Risky Decision-Making: A Retrospective Analysis of Brain Injury on the Rodent Gambling Task

Abstract: Decision-making is substantially altered after brain injuries. Patients and rats with brain injury are more likely to make suboptimal, and sometimes risky choices. Such changes in decision-making may arise from alterations in how sensitive individuals are to outcomes. To assess this, we compiled and harmonized a large dataset from four studies of TBI, each of which evaluated behavior on the Rodent Gambling Task (RGT). We then determined whether the following were altered: (1) sensitivity to overall contingenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…One study found that animals with high and low motor impulsivity differed in their preference of the different choices; animals in the low motor impulsivity group chose P2 more, animals in the high motor impulsivity group chose P1 and P4 more, while choice of P3 did not differ ( Barrus et al, 2015 ). This relationship between choice preferences corroborates our finding that options P1 and P2, that in standard scoring approaches are combined, does not seem to represent the same thing for the animals ( Vonder Haar et al, 2022 ). A recent study used cluster analysis to find choice phenotypes and found five distinct clusters: one with strong P2 preference, one with moderate P2 preference, one P3-preferring, one P4-preferring, and lastly a group with P1 and P3 preference ( Vonder Haar et al, 2022 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One study found that animals with high and low motor impulsivity differed in their preference of the different choices; animals in the low motor impulsivity group chose P2 more, animals in the high motor impulsivity group chose P1 and P4 more, while choice of P3 did not differ ( Barrus et al, 2015 ). This relationship between choice preferences corroborates our finding that options P1 and P2, that in standard scoring approaches are combined, does not seem to represent the same thing for the animals ( Vonder Haar et al, 2022 ). A recent study used cluster analysis to find choice phenotypes and found five distinct clusters: one with strong P2 preference, one with moderate P2 preference, one P3-preferring, one P4-preferring, and lastly a group with P1 and P3 preference ( Vonder Haar et al, 2022 ).…”
Section: Discussionsupporting
confidence: 88%
“…This relationship between choice preferences corroborates our finding that options P1 and P2, that in standard scoring approaches are combined, does not seem to represent the same thing for the animals (Vonder Haar et al, 2022). A recent study used cluster analysis to find choice phenotypes and found five distinct clusters: one with strong P2 preference, one with moderate P2 preference, one P3-preferring, one P4-preferring, and lastly a group with P1 and P3 preference (Vonder Haar et al, 2022). Once again this indicates that the relationship between the choices in the rGT is not as simple as P1 and P2 being perceived as advantageous and P3 and P4 as disadvantageous.…”
Section: Individual Choices During End Performancesupporting
confidence: 89%
“…A publicly-available dataset of behavior on this task [21] collected by our laboratory, which we refer to as the "control set" was used to inform simulation parameters. For the current study, only stable post-injury data (i.e., collected outside the initial task-learning and acute injury phases) were considered, and data involving manipulations (e.g., treatments) other than brain injury were excluded.…”
Section: Datasetsmentioning
confidence: 99%
“…A second dataset assessing this task, which we refer to as the "validation set" was obtained from Dr. Catharine Winstanley and is fully described elsewhere [22]. In brief, this dataset consisted of 14 studies of rats learning the RGT.…”
Section: Datasetsmentioning
confidence: 99%
See 1 more Smart Citation